University teachers' self-perception of digital research competencies. A qualitative study conducted in Peru - Suyo-Vega, Josefina Amanda; Meneses-La-Riva, Monica Elisa; Fernández-Bedoya, Víctor Hugo; Ocupa-Cabrera, Hitler Giovanni; Alvarado-Suyo, Sofía Almendra; da Costa Polonia, Ana; Miotto, Angélica Inês; Gago-Chávez, Johanna de Jesús Stephanie (Frontiers in Education, 2022)
Previous research warns about the limitations that some university teachers in Ibero-America have in relation to digital research competencies. The objective of this research was to analyze the research competencies from the university teacher's self-perception, contrasted with the classroom evaluation. The study had a qualitative approach. Interviews were conducted via the Zoom virtual platform, and recordings (of an average of four hours each) of classes delivered by ten teachers with an average age of 57 years in charge of scientific research courses at the postgraduate level in Peruvian universities were analyzed. The instruments used included an in-depth interview guide and a checklist. The results show that university teachers perceive themselves as specialists in the area of research, however, they present limitations when transmitting knowledge during the teaching-learning process. There is evidence of a lack of pedagogy, as well as limitations in the use of digital resources and technological tools due to their resistance to change. The conclusions reveal that it is key to make teachers aware of the paradigm shift, with a teaching that includes as digital competencies: knowing how to create and manipulate data, knowing how to use programs and information systems, knowing how to socialize and collaborate in digital environments, knowing how to exercise and respect a digital citizenship, knowing how to manage knowledge assertively, and, as we propose in this paper, knowing how to be a researcher in a digital environment.